2011
DOI: 10.1080/09585192.2011.560870
|View full text |Cite
|
Sign up to set email alerts
|

Four ‘domains’ of career success: how managers in Nigeria evaluate career outcomes

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 54 publications
5
84
1
Order By: Relevance
“…Studies on Nigerian managers by Ituma et al (2011) and on Chinese entrepreneurs by Lau et al (2007) also identified financial attainment as one of the prevailing career success dimensions in non-Western contexts. These findings reinforce our arguments that achievement can be conceptualized as a universal success factor.…”
Section: Global Profile Of Career Success Conceptualizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on Nigerian managers by Ituma et al (2011) and on Chinese entrepreneurs by Lau et al (2007) also identified financial attainment as one of the prevailing career success dimensions in non-Western contexts. These findings reinforce our arguments that achievement can be conceptualized as a universal success factor.…”
Section: Global Profile Of Career Success Conceptualizationsmentioning
confidence: 99%
“…We deemed a qualitative design as ideal to uncover the meanings of career success in different work settings and in different national contexts (see Ituma, Simpson, Ovadje, Cornelius, and Mordi 2011). It answers the call for using qualitative methods in IB studies (Birkinshaw, Brannen, and Tung 2011), such as in comparative cultural research (Doz 2011).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, a person's career can also create a main part of their individuality, when "what you do" determines "who you are" (Briscoe et al, 2011). As a consequence of shifting career patterns, the importance of the subjective (intrinsic) career has been brought to the frontage (Ituma et al, 2011). The subjective or the intrinsic career refers to the intangible type and is measured in terms of psychological and dispositional factors such as job satisfaction, career satisfaction, sense of value, learning, and self-awareness.…”
Section: The Concept Of Career Advancement (Ca)mentioning
confidence: 99%
“…Subjective career success is an evaluation of how an employee views their career; criteria are based on pointers regarding commitment and satisfaction; therefore, it is a reflection of their perceptions, emotions, and attitudes toward their career (Feldman and Ng, 2007). When evaluating success based on a subjective scale, employees may also evaluate their success in terms of managing their work-life balance and a sense of fulfillment (Ituma et al, 2011). In accordance with the literature, this study will take both subjective and objective patterns into consideration when measuring career success.…”
Section: Career Successmentioning
confidence: 99%